2020
DOI: 10.1177/0269215520907669
|View full text |Cite
|
Sign up to set email alerts
|

Group-based music intervention in Parkinson’s disease – findings from a mixed-methods study

Abstract: Objective: To evaluate a group-based music intervention in patients with Parkinson’s disease. Design: Parallel group randomized controlled trial with qualitative triangulation. Setting: Neurorehabilitation in primary care. Subjects: Forty-six patients with Parkinson’s disease were randomized into intervention group ( n = 26), which received training with the music-based intervention, and control group ( n = 20) without training. Interventions: The intervention was delivered twice weekly for 12 weeks. Main meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 44 publications
1
52
0
2
Order By: Relevance
“…A possible explanation might be related to the lack of precision in the Tinetti test to measure gait parameters and the quality of walking in the aftermath of stroke [ 14 , 31 ]. Consistently with previous literature, we found that rhythmic auditory stimulation in combination with conventional physiotherapy was not effective in improving balance [ 8 , 32 ]. Our research gave similar results for the two groups with regards to gait and fall risk, using the Timed Up&Go test, unlike other studies [ 14 , 28 , 31 , 33 ].…”
Section: Discussionsupporting
confidence: 91%
“…A possible explanation might be related to the lack of precision in the Tinetti test to measure gait parameters and the quality of walking in the aftermath of stroke [ 14 , 31 ]. Consistently with previous literature, we found that rhythmic auditory stimulation in combination with conventional physiotherapy was not effective in improving balance [ 8 , 32 ]. Our research gave similar results for the two groups with regards to gait and fall risk, using the Timed Up&Go test, unlike other studies [ 14 , 28 , 31 , 33 ].…”
Section: Discussionsupporting
confidence: 91%
“…Screening of titles and abstracts resulted in 71 articles which were used for further assessment. A total of 17 studies (18 articles) 19,20,22,23,25,[35][36][37][38][39][40][41][42][43][44][45][46][47] were included in this study (Figure 1). received rehabilitation training in the setting of music, like dancing, 20,22,23,25,[37][38][39][40][41][42][43]46 and walking.…”
Section: Search Resultsmentioning
confidence: 99%
“…The PEDro score ranged from 4 to 8, with a mean score of 6.18. Out of the 17 studies, 15 studies (16 articles) 20,22,23,25,[35][36][37][38][39][40][42][43][44][45][46][47] were considered high quality, whereas two studies 19,41 were considered low quality (Table 2).…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations